Optimal Criteria of Investment Potential in Innovation Cycles of the Economic System of Agro-Industrial Enterprises. - Trusova, Natalia; Трусова, Наталя Вікторівна; Hryvkivska, Oksana; Kukina, Natalia; Кукіна, Наталя Володимирівна; Kotvytska, Natalia; Makarenko, Petro; Pilyavsky, Volodymyr (Economic Affairs, 2023)
ENG The purpose of the study is to find the optimal criteria for investment potential in innovative cycles of the economic system of agro-industrial enterprises of Ukraine. A methodical approach is presented to determine the optimal criteria of investment potential with strategic changes in the innovation cycles of the economic system of agro-industrial enterprises, which formed sources of investment for expanded reproduction and stimulation of resource opportunities according to defined innovation priorities. Sources and a block diagram of the step-by-step balancing of sources of investment potential in innovation cycles of the economic system of agro-industrial enterprises are presented. The interpretation of the possibilities of investment potential based on the coefficient of strategic changes in the innovation cycles of the economic system is substantiated. The distribution of organizations and their activities regarding scientific developments of modern innovation cycles in the economic system of agro-industrial enterprises of Ukraine by sectors of activity was carried out. The “corridor” of opportunities for investment potential with strategic changes in the innovation cycles of the economic system of agro-industrial enterprises of Ukraine at the unique, marginal and average levels have been determined.////////////// UKR Метою дослідження є пошук оптимальних критеріїв інвестиційного потенціалу в інноваційних циклах економічної системи агропромислових підприємств України. Представлено методичний підхід до визначення оптимальних критеріїв інвестиційного потенціалу при стратегічних змінах інноваційних циклів розширеної економічної системи агропромислових підприємств, які формували джерела інвестицій для відтворення та стимулювання ресурсних можливостей відповідно до визначених інноваційних пріоритетів. Наведено джерела та блок-схему поетапного збалансування джерел інвестиційного потенціалу в інноваційну діяльність, представлено цикли економічної системи підприємств АПК. Інтерпретовано можливості інвестиційного потенціалу на основі коефіцієнта стратегічних змін в інноваційних циклах.
Оптимальні критерії інвестиційного потенціалу в інноваційних циклах економічної системи агропромислових підприємств.
Keywords: Agro-Technical Sphere; Competitiveness; Economic System; Innovation Projects; Investment Resources; агротехнічна сфера; конкурентоспроможність; інноваційні проекти; інвестиційні ресурси; економічна система